A world of gestures [videorecording] culture and nonverbal communication - Archer, Dane; Silver, Jon (Dane Archer, 1991)
Gestures are a form of nonverbal communication, a silent language unique to every society. This videotape explores gestures from cultures around the world. Shows the different types of gestures, including those for beauty, sexual behavior, suicide, aggression, friendship and love.